MODEL BIMBINGAN PERKEMBANGAN UNTUK MENINGKATKAN KECAKAPAN SOSIAL-PRIBADI ANAK BERBAKAT AKADEMIK - Rochmat Wahab (LPMPP Universitas Negeri Yogyakarta, 2010)
Abstract: A Development Guidance Model to Improve Academically GiftedChildrens Social-Personal Skills. This study intended to investigate theeffectiveness of personal-social guidance programs for Academically GiftedStudents (AGS). This study was a research and development study. The researchsubjects were 80 senior high students. The data were collected using an inventoryand rating scales. The quantitative data were analyzed by the the descriptive andinferential statistical techniques, i.e. percentile, t-test and ANOVA, and thequalitative data by the descriptive technique. The results show that (1) the profileof personal-social skills among the AGS is very good, (2) the materials andimplementation of the Personal-Social Guidance Program Guide on the basis of theDevelopment Model is an appropriate alternative model that can increase theAGSs personal-social skills, (3) the Personal-Social Guidance Program Guide onthe basis of the Developmental Model is empirically proven to be able to increasethe AGSs personal-social skills.Keywords: development guidance model, social-personal guidance, academicallygifted students